The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1159/000067963
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Changes in Dietary Fatty Acids during Pregnancy on Placental and Fetal Fatty Acid Profile in the Rat

Abstract: To determine whether the composition of long-chain polyunsaturated fatty acids (PUFA) could be modified in the fetus by maternal dietary fatty acids, pregnant Sprague-Dawley rats were fed semipurified diets that differed only in the non-vitamin lipid component. The diets contained either 10 g palm, sunflower, olive or fish oil (FOD)/100 g diet. A total of 5–6 rats were studied in each group. At day 20 of gestation, corresponding to 1.5 days prior parturition, the fatty acids in maternal adipose tissue were clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 43 publications
5
22
1
Order By: Relevance
“…Laws, Laws, Lean, Dodds and Clarke transported across the placenta more readily than those found in the other oils studied, although this theory is unlikely as it contradicts data from studies in rats and humans (Haggarty et al, 1997;Amusquivar and Herrera, 2003;Larque et al, 2003;Ortega and Herrera, unpublished data). Recent research has suggested that the type of dietary fat rather than the total fat content of the diet is important in determining neonatal outcome (Jean and Chiang, 1999;Rooke et al, 2001a, b and c).…”
Section: --mentioning
confidence: 79%
“…Laws, Laws, Lean, Dodds and Clarke transported across the placenta more readily than those found in the other oils studied, although this theory is unlikely as it contradicts data from studies in rats and humans (Haggarty et al, 1997;Amusquivar and Herrera, 2003;Larque et al, 2003;Ortega and Herrera, unpublished data). Recent research has suggested that the type of dietary fat rather than the total fat content of the diet is important in determining neonatal outcome (Jean and Chiang, 1999;Rooke et al, 2001a, b and c).…”
Section: --mentioning
confidence: 79%
“…It is important to note that the percentage of AA in FFAs was inversely correlated with the expression of all membrane proteins and also with the cytosolic proteins A-FABP and B-FABP. Several studies (27,28) in animals suggest that EPA and AA are competitors for the desaturation and elongation pathway, and this competition might explain the negative correlations with FABP and AA in the placenta, because the percentage of AA was not different in any of the placental lipid fractions among the supplemented groups (results not shown).…”
Section: Tablementioning
confidence: 95%
“…Student's t test was used to compare values between olive oil and fish oil groups within the same day and are shown by asterisks: *p \ 0.05, **p \ 0.01, ***p \ 0.001. Tukey's test was used to determine differences between different time points after one-way ANOVA and shown by small letters in the olive oil group and by capital letters in the fish oil group (different letters indicating statistically significant differences, p \ 0.05) Lipids (2010) 45:409-418 415 diet it has been demonstrated that this fatty acid is retained in adipose tissue during late pregnancy at a higher proportion that any other LCPUFA [45]. It is, therefore, proposed that DHA after being taken up and stored in adipose tissue during the first half of pregnancy is mobilized during late pregnancy and the first days of lactation, when lipolytic activity is highly enhanced [17,46,47], becoming available to the mammary gland for milk synthesis.…”
Section: Dietary Supplement During the First Half Of Gestationmentioning
confidence: 99%
“…The influence of dietary fatty acids during lactation on milk fatty acid composition has been well recognized in humans [19,55,56] and has been associated to the fatty acid composition in maternal adipose tissue [29,30]. Dietary fatty acids during pregnancy in rats have been shown to determine their proportion in maternal adipose tissue [45,57,58], and feeding tuna oil in sows during late pregnancy is known to affect fatty acid composition in newborn piglet tissues and plasma [8,59].…”
Section: Dietary Treatment During the Second Half Of Gestationmentioning
confidence: 99%